Recent Advances in Ocean Nuclear Power Plants - Kang-Heon Lee; Min-Gil Kim; Jeong Ik Lee; Phill-Seung Lee (Energies, 2015)
In this paper, recent advances in Ocean Nuclear Power Plants (ONPPs) are reviewed, including their general arrangement, design parameters, and safety features. The development of ONPP concepts have continued due to initiatives taking place in France, Russia, South Korea, and the United States. Russia’s first floating nuclear power stations utilizing the PWR technology (KLT-40S) and the spar-type offshore floating nuclear power plant designed by a research group in United States are considered herein. The APR1400 and SMART mounted Gravity Based Structure (GBS)-type ONPPs proposed by a research group in South Korea are also considered. In addition, a submerged-type ONPP designed by DCNS of France is taken into account. Last, issues and challenges related to ONPPs are discussed and summarized.